Eco-design based on ontology: Historical evolution and research trends - Mohammed, Moseed; Awanis, Romli; Rozlina, Mohamed (AIP Publishing LLC., 2021)
Sustainability assessment has received more and more focused on developing the sustainable products through integrating the three main components which are economic dimension, environmental goals, and social requirements, these components have become essential to product innovations that protect environment and public health throughout their entire life cycle, from extracting raw materials to end of life. The difficulty facing the manufacturer is the economic, social and environmental impacts of sustainable development with lack of integration between sustainability criteria and product design process. The aim is to produce and design sustainable products and easy the use of environmental, economic, and social assessment methods through sharing of product relevant information with minimal human intervention. As a result of the effective role of the ontology in the process of representing and evaluating the economic, environmental, and social impacts through the product life cycle, ontology will contribute to build comprehensive decisions in product sustainability in industrial.